SWOT ANALYSIS ON THE POTENTIAL OF DEVELOPING MASS SPORTS IN LAM DONG PROVINCE - Trần, Quốc Hùng (2022)
In recent years, mass sports have expanded globally and become an international movement of mankind, for all people. Mass sports have flourished in many areas of Vietnam. With favorable geographical position, Lam Dong povince has the potential to develop various and unique mass sports. This article uses the SWOT analysis technique to identify the strengths, weaknesses, opportunities and threats on the potential for mass sports development in Lam Dong.